Pengaruh Ekonomi Syariah terhadap Implementasi Sistem Keuangan di PT Pesat Jaya Persada - Bakti Toni Endaryono; Nurti Nurhayati; Yanti Hasbian Setiawati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2019)
This study aims to analyze and find out about the influence of Islamic economics on the implementation of the financial system at PT. Pesat Jaya Persada. The method used in this study using quantitative methods is one type of research whose specifications are systematic, planned, and clearly structured from the beginning to the design of the research. with the results of the study Calculation of the total score of variables X and Y using the correlation formula obtained R of 0.846, while the coefficient is determined r that is 71.54 or equivalent to 71.54%. Significant whether or not the correlation of variable X and variable Y was consulted with table r with a confidence level of 0.05 N = 10 obtained R table 0.632 or 0.632 <0.846. and t test results obtained T count greater than t table (6.09> 2.23). It was concluded that there was a significant relationship between variable X and Y. Based on the number of respondents as many as 10 people, with a total score of 819, the highest score of 119, the lowest score of 48, Range: 71, Length of Class 12, Average 85.75, mode: 75, Median: 76, Deviation Deviation: 22.64. Calculations obtained Y of 6.38 were consulted with the chi square price table (X) at a significant level of 0.05 and db = k-1 = 19-1 = 18 obtained by chi table 15.50 Thus the Y count is smaller than the Y table (6.38 <15.50) so concluded normal distribution. Concern between the Islamic economy and the implementation of the financial system is about 71.54% in this study, which emphasizes the research on the company PT Pesat Jaya Persada.